Plasma cell gingivitis – an unusual case of simultaneus disease occurence in two siblings - Đurić, Milanko; Veljović, Tanja; Gušić, Ivana; Mirnić, Jelena; Vučković, Nada; Petrović, Đorđe (Vojnosanitetski pregled, 2021)
Abstract Introduction. Plasma cell gingivitis (PCG) is a relatively rare disease that usually occurs on the anterior maxillary and mandibular gingiva. It manifests as extreme redness, swelling and gum tissue enlargement with propensity for bleeding, accompanied by extensive infiltration of plasma cells in the lamina propria. While the disease etiology remains unclear, its presentation is mostly attributed to nonspecific inflammatory reaction to certain foodstuffs or ingredients in oral hygiene products. Case report. A 9-year-old boy and 11-year-old girl were brought for exam by their mother because of fiery red lesions on the gingiva. The lesions had the same clinical features and identical localization and were concomitantly present in both siblings. After excluding other oral or systemic diseases with similar clinical manifestations, a diagnosis of PCG was established (most likely due to chewing gum). Conclusion. While beeing a purely benign, the PCG clinical appearance may mask much more detrimental conditions. Consequently, each such lesion requires due attention. To date, familial tendency for the development of such a condition has not been reported.
Keywords: gingivitis; plasma cells; diagnosis, differential; histological techniques